Human Resources Development as the Future Agenda of 21st Century Indonesian Ecclesiology in the Realm of Economic Digitalisation - Halim Wiryadinata; Sonny Eli Zaluchu; Susi Susi; Roni Roni (Jurnal Manajemen Indonesia, 2023)
This research seeks the priority of human resources development in Indonesian ecclesiology as the response to economic digitalization growth. The COVID-19 pandemic has created vast changes in the economic market and needs a long-term strategy in human resources management. As a community of people, a church needs to pursue the future agenda of 21st-century ecclesiology. Through the conducting of the sociology of religion method, this research finds out the old concept of ecclesiology and needs to improve as the immediate response for eliminating human resources. The study concludes by showing human resources as the priority agenda for development in economic digitalization. Keywords— Human Resources Management; Indonesian Ecclesiology; Future Agenda of Church; Economic Digitalisation